Pre-service science teacher’s misconceptions of the chemical bonds - Nur Farha Shaafi; Nurul Nabilla Mohammad Khalipah; Nabilah Abdulla (Perpustakaan Tun Abdul Razak, UiTM, 2023)
Science teachers in Malaysia could enter the profession via a science education degree programme, or by taking a diploma in education after completing a separate degree in pure science. Misconceptions of key concepts such as chemical bonds are a highlighted issue among pre-service science teachers. The objectives of this study were to: (i) identify the scientific and non-scientific conceptions of chemical bonds held by pre-service science teachers, (ii) identify factors that influence pre-service science teachers’ conceptions, and (iii) offer strategies to overcome preservice science teachers’ misconceptions about chemical bonds. A mixed-method research methodology (qualitative and quantitative) i.e., paper-and-pencil test, and openended interview was adopted. Thirty respondents consisting of pre-service teachers in Science Education (majoring in Chemistry) from a Faculty of Education in a public university in Malaysia were non-randomly selected based on the purposive sampling technique. Our findings showed a high level of misconceptions that also did not alter significantly through the respondents’ four years of training. The correct scientific conceptions about key concepts such as chemical bonds should be comprehensively strengthened among pre-service science teachers before they graduate to ensure that they can deliver the best quality chemistry knowledge to their future students.